Analisis Penggunaan Unsur Sensualitas Sebagai Bentuk Pelanggaran Etika Periklanan Studi Kasus Pada Iklan Televisi Pompa Air Shimizu - Yusnaidi Yusnaidi (Jurnal Bisnis Dan Kajian Strategi Manajemen, 2018)
Abstract                                                                   This research is designed to anylize the tv advertisings which have been disobeyed  marketing ethics because the used of  women sexuality. It is  a fact that tv ads is one of the effective advertising channel to promotes a product and enhance the corporate image. However there are a lot of misconducts  in implementing tv ads to persuade consumers by showing conversations and scenes with a lot of sexual images. Sexual images in the ads are happened in many marketing events and programs. It has been considered as the effective approach to attract consumers attention and the message would be easy to be remembered and internalized in the memory. This phenomena also had happened in Indonesia where tv ads content sexual images which had caused controversy and rejection among the consumers and authorities. It againts Indonesian Advertising Code of Conduct. The sample of tv ads which content sexual images in Indonesia and considered of being unethical was the ad of Shimizu Water Pump. This tv ads had appeared on the national tv channel in 2011 and a lot of negative words, sexual images and the moves that could be seen as pornographic actions. There were several researchs had been conducted on the issue of ethics in advertising industry. Therefore this research strengthen previous researchs which have  concluded that ethics should be implemented inadvertising industry and no room for misconduct behaviour for this rule. The observations methods and qualitative research approach are part of the analyzing process to reach the objective and conclude the phenomena.Keywords : Shimizu Waterpump, tv ads, ethical advertising, business ethics.